Impact of Work-Fit Stretching on Occupational Fatigue Among Industrial Sewing Operators - Sumardiyono Sumardiyono; Yunita Anisa Putri; Warda Yussy Rha (Universitas Airlangga, 2025)
Introduction: Garment sewing employees are exposed to great fatigue factors of long-term static and monotonous works, which affect their productivity and safety. Although Work-Fit Stretching has been proven to be effective in the alleviation of muscle fatigue, possibilities are scarce regarding sewing workers in developing nations. The paper is a review of the impact of ergonomics-predicting stretching action as a time step fatigue action. Methods: This is a randomized controlled trial study with 128 sewing operators utilized, who were distributed in a Work-Fit Stretching group and a control group. The intervention took one month that consisted of two sessions a day, five days per week. The reaction timer was used three times to measure occupational fatigue and analyzed in SPSS by independent t-tests and Repeated measures ANOVA. Results: The findings indicated that Work-Fit Stretching program work-depressed the occupational fatigue in sewing workers. A statistically significant difference was observed between the intervention and the control groups in the post-test measurement (p < 0.001), the effect sizes were medium to large (0.670 to 1.117 according to Cohen). Repeated Measures ANCOVA has shown a significant aspect of decreasing the fatigue as the time goes by (p < 0.001; Partial Eta 2 = 0.218), which indicates that the intervention was both statistically and practically effective. Conclusion: Use of Ergonomic-based stretching was very useful in eradicating work fatigue of the sewing operators with moderate-to-large effects maintained across age and years to service. The method is easy and applicable in difficult routine working environments.